FAKTOR PENENTU KINERJA PERUSAHAAN PADA SUBSEKTOR BARANG PERINDUSTRIAN DI BURSA EFEK INDONESIA - RIANDY DEA NOVA; SATRIYO WIBOWO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study examines the effect of cash holding, firm size, leverage, asset turnover, intensity, and growth on firm performance in the industrial goods subsector listed on the Indonesia Stock Exchange during the 2015–2024 period. This research employs a quantitative approach using panel data from 130 firms selected through purposive sampling. Data were analyzed using a fixed effect panel regression model with EViews 12. Firm performance is measured by Return on Assets (ROA). The results indicate that firm size, leverage, intensity, and growth have a significant effect, whereas cash holding and asset turnover do not significantly affect firm performance These findings suggest that effective capital structure management, asset utilization, and growth strategies are essential for improving firm performance.